2005
DOI: 10.1038/modpathol.3800337
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression alterations in the non-neoplastic parenchyma adjacent to infiltrating pancreatic ductal adenocarcinoma

Abstract: The non-neoplastic pancreatic parenchyma adjacent to infiltrating ductal adenocarcinoma demonstrates inflammation, fibrosis, acinar cell loss and small duct-like metaplasia of acinar cells. Similar morphologic changes are also observed in the setting of chronic pancreatitis. In addition, peritumoral acini have been shown to have alterations in gene expression even in the absence of morphological changes. To better understand the pancreatic acinar responses to infiltrating pancreatic ductal adenocarcinoma, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 20 publications
1
43
1
Order By: Relevance
“…In addition, the use of microarrays allowed gene expression patterns to be characterized in pancreatic acinar tissue adjacent to infiltrating PDAC. The most abundantly expressed gene was Reg3b itself, which increased over 100-fold (35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of microarrays allowed gene expression patterns to be characterized in pancreatic acinar tissue adjacent to infiltrating PDAC. The most abundantly expressed gene was Reg3b itself, which increased over 100-fold (35).…”
Section: Discussionmentioning
confidence: 99%
“…Despite enormous efforts, relevant markers useful for screening have been established in only a few tumor types (13,14 ), and no studies have found markers for early detection of pancreatic cancer (15)(16)(17)(18)(19). 2-DE, especially in combination with microdissection, seems an appropriate tool (19 ), but proteins in the peptide interval, as well as those of high hydrophobicity or of extreme isoelectric points, are difficult to separate and hence are typically neglected, resulting in a loss of potentially interesting proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the application of cDNA and TMAs for the detection of protein or gene alterations in human pancreatic non-neoplastic and cancer tissues is a reliable method of analysis [27][28][29][30] . Compared with their corresponding traditional larger sections, TMAs have been proven to provide concordant results in immunohistochemical studies, especially if they contain two or three cores from each case [31,32] .…”
Section: Discussionmentioning
confidence: 99%